1996
DOI: 10.1016/s0960-9822(02)00480-3
|View full text |Cite
|
Sign up to set email alerts
|

Sertoli cell signaling by Desert hedgehog regulates the male germline

Abstract: Dhh expression in pre-Sertoli cells is one of the earliest indications of male sexual differentiation. Analysis of a null mutant demonstrates that Dhh signaling plays an essential role in the regulation of mammalian spermatogenesis. Loss of Patched expression in Dhh mutants suggests a conservation in the Hedgehog signaling pathway between flies and mice, and indicates that Leydig cells may be the direct target of Dhh signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
447
1
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 600 publications
(472 citation statements)
references
References 32 publications
19
447
1
5
Order By: Relevance
“…Paramantier et al12 found that the peripheral nerves of dhh null mutant mice showed minifascicular formation. Analysis of null mutant mice demonstrated that dhh signaling plays an essential role in the regulation of mammalian spermatogenesis 13. Because mammalian hedgehog genes share a striking homology to the Drosophila segment polarity hedgehog gene, these findings suggest that DHH plays crucial roles in both peripheral nerve sheath development and spermatogenetic regulation in humans.…”
Section: Discussionmentioning
confidence: 98%
“…Paramantier et al12 found that the peripheral nerves of dhh null mutant mice showed minifascicular formation. Analysis of null mutant mice demonstrated that dhh signaling plays an essential role in the regulation of mammalian spermatogenesis 13. Because mammalian hedgehog genes share a striking homology to the Drosophila segment polarity hedgehog gene, these findings suggest that DHH plays crucial roles in both peripheral nerve sheath development and spermatogenetic regulation in humans.…”
Section: Discussionmentioning
confidence: 98%
“…Unlike SHH, which is required for the development of seemingly all organs, the role of IHH and DHH is restricted to a more limited number of tissue-specific developmental events, e.g. bone morphology and gonadal differentiation, respectively (Bitgood et al, 1996;St-Jacques et al, 1999).…”
Section: Hh Signaling: a Master Regulator Of Developmentmentioning
confidence: 99%
“…Within this cell population we identified genes known to be important for testes development or as preSertoli cell markers, including Sox9, Amh/Mis, Dhh, Sf1/Nr5a1, Gata4, Gata6, Dmrt1, Fgf9, and Ptgds (Ikeda et al, 1994;Bitgood et al, 1996;Kent et al, 1996;Morais da Silva et al, 1996;Ketola et al, 1999;Colvin et al, 2001;Adams and McLaren, 2002;Tevosian et al, 2002;Malki et al, 2005;Wilhelm et al, 2005). Notably, HybSRYp-RFP expressing cells did not express markers for germ cells, such as Oct4 and Ssea-1, or markers for endothelial cells, such as Ntrk3.…”
Section: Fluorescent Hybsryp-rfp Cells Express Presertoli Cells Markementioning
confidence: 99%